Modulation effects of danshen-honghua herb pair on gut microbiota of acute myocardial ischemia model rat. Issue 1 (29th March 2022) - Du, Shao-Bing; Zhou, Hui-Hui; Wang, Peng-Fei; Wang, Xiao-Ping; Xue, Zhi-Peng; Li, Jing; Gao, Su; Li, Na; Bai, Ji-Qing; Xie, Li-hong
Abstract: In the recent years, a growing number of studies have shown that the occurrence of myocardial ischemia (MI) is closely related to the gut microbiota (GM). The Danshen-Honghua herb pair (DHHP), a classic combination in traditional Chinese herbal formulas, has been widely applied throughout history to cure cardiovascular disease, exhibiting remarkable clinical efficacy to treat ischemic heart disease (IHD). However, the intrinsic regulation mechanism of DHHP in treating MI remains unclear. This study aims to investigate the possible protective mechanism of DHHP in rats with acute myocardial ischemia (AMI) induced by isoproterenol (ISO) through 16S rRNA gene sequencing technique. Pharmacodynamic results showed that DHHP significantly ameliorated the pathological changes and improved the abnormal cardiac enzymes levels in the AMI rats. In addition, GM analysis demonstrated that DHHP effectively ameliorated the ISO-induced dysbiosis of the GM community, mainly by enhancing the GM diversity and increasing the relative abundance of Bacteroides, Roseburia, unclassified_f__Lachnospiraceae, and Lachnospiraceae_NK4A136_group, the abundance ratio of Bacteroidetes to Firmicutes, and decreasing the relative abundance of Escherichia-Shigella and Enterococcus . In summary, this study revealed that DHHP could improve ischemic myocardial injury in rats, and that its regulation mechanism is associated with significantly ameliorating the composition of GM, thus contributing to further our understanding of the anti-MI mechanisms of DHHP. Abstract : The strategy of exploring the possible mechanism of DHHP treating AMI.